Quantifying the effects of land-use change on wildlife in Kapit region, Sarawak - Zen, Irina Safitri; Ismail, Khairunaim; Mohd Hashim, Nor Hanisah; Trihatmoko, Edy (IIUM Press, 2025)
This study investigates the impact of forest land-use change on wildlife populations within the Kapit Forest Management Unit (FMU) in Sarawak, Malaysia, between 2011 and 2020. The methodology involved analysing primary forest cover data using GIS-based remote sensing to quantify land-use changes, evaluating wildlife populations and forest loss using correlation analysis, and performing relative abundance analysis coupled with observation on site, particularly in protected areas. Results show a moderate negative correlation (r = -0.48) between forest loss and wildlife population decline, with the highest relative wildlife abundance recorded in 2011 (15.41%). Wildlife abundance subsequently decreased, attributed to habitat degradation and human pressures. Dominant bat species included Cynopterus brachyotis and Penthetor lucasi, each comprising 17.4% of captures, while Dycopterus spadiceus and Kerivoula intermedia showed moderate abundances of 10.9% and 8.7%. Although approximately 20% of the land is designated for conservation, including Baleh Protected Forest, it is insufficient to offset the surrounding impacts of infrastructure development. The findings demonstrate that current Sustainable Forest Management (SFM) practices are inadequate to prevent biodiversity loss. Strengthening conservation policies, enforcement mechanisms, sustainable land-use planning, habitat restoration, and community engagement are essential to balancing production and conservation, and to enhancing ecosystem resilience within the Kapit FMU.